Finite element analysis of beams on no- tension foundation - Le, Nguyen Van (Vietnam Journal of Mechanics, 1982)
In this paper a finite element analysis of beams on no-tension foundation is presented. To establish the algorithm the Winder's model of the foundation is used it is assumed that the total stiffness of the structure consists of the stiffness of the beam and the stiffness of the foundation. The no-tension property of the foundation is taken in-to account by eliminating the stiffness of the foundation at the place where the tensional reaction occurred. Some numerical examples are illustrated to point out the effect of the separation of the beam from the foundation to the internal forces or the beam.